2003
DOI: 10.1021/je025533x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature- and Pressure-Induced Crystallization and Melting of Tetracontane in Propane:  Evidence of Retrograde Crystallization

Abstract: The crystallization and melting transitions for tetracontane in propane, measured in this work at pressures up to about 1200 bar, are found to exhibit a temperature minimum, which implies crystallization upon decompression (retrograde crystallization). The supercooling effect, which is the difference between the crystallization and melting temperature, is found to decrease with increasing tetracontane concentration. The transitions induced by varying temperature at constant pressure are found to fall near the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 2 publications
(4 reference statements)
1
26
0
Order By: Relevance
“…ment with the results of Łuszczyk and Radosz[3] is very good. The extension of the retrograde region is similar to those observed by Łuszczyk and Radosz.…”
supporting
confidence: 52%
See 3 more Smart Citations
“…ment with the results of Łuszczyk and Radosz[3] is very good. The extension of the retrograde region is similar to those observed by Łuszczyk and Radosz.…”
supporting
confidence: 52%
“…However, it is not clear whether the solid-liquid curve is monotonic also in binary mixtures containing lowconcentrations of the heavy component. An example of an unusual shape of the solid-liquid curve in dilute nonpolar mixtures has been reported by Łuszczyk and Radosz [3] for the system propane + tetracontane. In this work for the first time it was shown that in a binary type V mixture it is possible to observe retrograde melting.…”
Section: Solid-liquid Equilibria In the System Propane + Tetracontanementioning
confidence: 78%
See 2 more Smart Citations
“…More detailed descriptions are available elsewhere. [13][14][15] The CP is determined to be the inflection point of the TLI curve, which corresponds to a peak in its first derivative. Sample graphs of two typical cases of SLI curves are shown in Figures 13.4 and 13.5.…”
Section: Early Feasibility Studies On Model Systemsmentioning
confidence: 99%